The Molecular Chaperone Hsp70 Activates Protein Phosphatase 5 (PP5) by Binding the Tetratricopeptide Repeat (TPR) Domain - Connarn, Jamie N. (American Society for Biochemistry and Molecular Biology, 2014)
Protein phosphatase 5 (PP5) is auto-inhibited by intramolecular interactions with its tetratricopeptide repeat (TPR) domain. Hsp90 has been shown to bind PP5 to activate its phosphatase activity. However, the functional implications of binding Hsp70 to PP5 are not yet clear. In this study, we find that both Hsp90 and Hsp70 bind to PP5 using a luciferase fragment complementation assay. A fluorescence polarization assay shows that Hsp90 (MEEVD motif) binds to the TPR domain of PP5 almost 3-fold higher affinity than Hsp70 (IEEVD motif). However, Hsp70 binding to PP5 stimulates higher phosphatase activity of PP5 than the binding of Hsp90. We find that PP5 forms a stable 1:1 complex with Hsp70, but the interaction appears asymmetric with Hsp90, with one PP5 binding the dimer. Solution NMR studies reveal that Hsc70 and PP5 proteins are dynamically independent in complex, tethered by a disordered region that connects the Hsc70 core and the IEEVD-TPR contact area. This tethered binding is expected to allow PP5 to carry out multi-site dephosphorylation of Hsp70-bound clients with a range of sizes and shapes. Together, these results demonstrate that Hsp70 recruits PP5 and activates its phosphatase activity which suggests dual roles for PP5 that might link chaperone systems with signaling pathways in cancer and development.